2016
DOI: 10.1080/19490976.2016.1215805
|View full text |Cite
|
Sign up to set email alerts
|

Limited prolonged effects of rifaximin treatment on irritable bowel syndrome-related differences in the fecal microbiome and metabolome

Abstract: Irritable bowel syndrome (IBS) is a chronic functional disorder and its development may be linked, directly and indirectly, to intestinal dysbiosis. Here we investigated the interactions between IBS symptoms and the gut microbiome, including the relation to rifaximin (1200 mg daily; 11.2 g per a treatment). We recruited 72 patients, including 31 with IBS-D (diarrhea), 11 with IBS-C (constipation), and 30 with IBS-M (mixed constipation and diarrhea) and 30 healthy controls (HCs). Of them, 68%, 64%, and 53% pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 81 publications
4
57
1
Order By: Relevance
“…Given the drugs beneficial effects in patients with IBS with diarrhoea, this would seem paradoxical. Studies that have evaluated the effect of rifaximin on the microbiome, show that any changes are limited, and are not sustained . Although the limited research regarding rates of C. difficile infection and microbial resistance are reassuring, continued monitoring of patients receiving repeated courses of the drug will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Given the drugs beneficial effects in patients with IBS with diarrhoea, this would seem paradoxical. Studies that have evaluated the effect of rifaximin on the microbiome, show that any changes are limited, and are not sustained . Although the limited research regarding rates of C. difficile infection and microbial resistance are reassuring, continued monitoring of patients receiving repeated courses of the drug will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that a 2-week course of treatment causes modest, but detectable, changes in microbial profiles of the feces (144,145). Other research studies evaluating fecal microbial profiles from IBS patients demonstrated that rifaximin effects on the microbiota were limited and not sustained (145)(146)(147).…”
Section: Quality Of Evidence: Moderatementioning
confidence: 99%
“…There is emerging evidence that gut microbiota play an important role in the development of IBS. 1 Recent reports have indicated that the composition of gut microbiota differs between patients with IBS and healthy individuals [2][3][4] and contributes to IBS pathophysiology. [5][6][7][8] Treatment with antibiotics, such as rifaximin, relieves global IBS symptoms without causing constipation, suggesting that there is a direct relationship between microbiota and IBS.…”
mentioning
confidence: 99%